If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying z + 12 = 9 Reorder the terms: 12 + z = 9 Solving 12 + z = 9 Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '-12' to each side of the equation. 12 + -12 + z = 9 + -12 Combine like terms: 12 + -12 = 0 0 + z = 9 + -12 z = 9 + -12 Combine like terms: 9 + -12 = -3 z = -3 Simplifying z = -3
| 6-2m=16 | | 11-4x=12+5x | | -4(5-2x)=12 | | -28=4(8-x) | | 100x^2-64= | | 19t-9-13t=39 | | 7x-9+7x=121 | | 6(k-1)-(5k-9)=-6 | | 3/4(2x+4)=x+19 | | -3x-9=-9 | | 5x+2y+2x+3y=180 | | x+4x-7=8 | | 6(x-1)+2(x-1)=10-5x | | 2(w+5)-7w=-5 | | 12n^3=-4n^2-3n-1 | | 40=9m+4 | | 5x+9(x+9)=179 | | -3x^2-11x+20=0 | | 40=x^2+2x | | ln(x)=-0.5 | | 4w^4-40w^2=44 | | 4m-3=7 | | -3x-10=-13 | | 5x-5=2x+45 | | (10x-3)=-2x+12 | | 6x+4+7x+2=5x+5 | | 3.75= | | 10x-3=-2x+12 | | n^4-4n^2=60 | | X^2+6x+y^2+10y=20 | | 3n/7-=1/8 | | U-7+8=19 |